IONOSPHERIC EFFECT OF NON-STORM HILDCAA (HIGH INTENSITY LONG DURATION CONTINUOUS AURORAL ACTIVITY) - Adhikari, Binod; Mishra, Roshan Kumar; Pandit, Drabindra; Bhattarai, Binod; Chapagain, Narayan Prasad (Journal of Institute of Science and Technology, 2017)
The magnetosphere of the Earth is temporarily changed by geomagnetic disturbances. Geomagnetic disturbances are caused by solar wind, shock wave or clouds of solar magnetic field. During their interactions energy is transferred into the magnetosphere. Apart from this, solar wind pressure also compresses the magnetosphere. Both kinds of interactions cause an increase in plasma movement through the magnetosphere and ionosphere. The geomagnetic disturbances may sustain for a few minutes to many hours depending upon the intensity of energy and particles released from the Sun. The geomagnetic disturbances are measured by geomagnetic indices for short periods of time. In this work, we discuss the impact of peculiar type of geomagnetic disturbances known as high intensity long duration continuous auroral activity on the Earth’s ionosphere. This analysis leads to understand the impact on communication system due to coupling between solar terrestrial environments. It will also broaden the various aspects on how ionospheric critical frequency (foF2), F2 layer peak density height (hmF2), high frequency (hF) and horizontal component of earth magnetic field can be lifted from lower to higher altitudes. Journal of Institute of Science and Technology Volume 22, Issue 1, July 2017, page: 34-40